Density-functional theory for excited states - Görling, Andreas (Physical Review A, 1996)
A Kohn-Sham formalism for the treatment of excited states within the density-functional theory (DFT) is presented DFT exchange and correlation energy functionals for excited states are denned. Explicit expressions for these functionals are derived by generalizing a recent DFT perturbation theory. A computauonal scheme for the treatment of excited states wuhin the DFT is suggested. Differences of Kohn-Sham eigenvalues are shown to be well-defined approximations for excitation energies. Correction terms to these approximations are presented Perturbation theory expansions for band gaps are discussed.